SOCIOECONOMIC PROFILE OF LIVESTOCK FARMERS AND ITS EFFECT ON UTILIZATION OF DIGITAL MARKETING TOOLS IN TARABA STATE, NIGERIA - Ashasim, T. I.; Mahmood, H. U.; Ornan, T. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the socioeconomic profile of livestock farmers and its effects on utilization of digital marketing tools in Taraba State, Nigeria. It specifically examined the socioeconomic characteristics of livestock farmers, factors influencing the use of digital marketing tools and the constraints to the utilization of digital marketing tools among livestock farmers. A multi-stage sampling procedure was employed to select 384 respondents for this study. Data were collected primarily through questionnaires administered to livestock farmers. The data collected were analyzed using descriptive statistics and logistic regression. The findings of the study revealed that, average age of livestock farmers was 41.4 years, with a significant majority being male (78%) and possessing tertiary education (76.0%). The livestock farmers had an average of 12.4 years of experience in livestock farming and 50% were members of a cooperative. The mean household size was eight members, and 50% of respondents had access to extension services. Reliance on personal savings was a common source of credit. Factors influencing the use of digital marketing tools included ease of use, age, extension contact, farm size, and sex. The main constraints were the high cost of digital devices, inadequate training or support on digital marketing, and fears of online fraud or scams. The study recommended that Taraba State Ministry of Agriculture and Food Security should facilitate the provision of affordable digital devices to livestock farmers through subsidy programmes, leasing schemes, or partnerships with telecommunications companies.